The South-East Asian crisis and the Indian economy - Yadav, Surendra S.; Jain, P.K. (1999)
The South-East(SE) Asian Crisis has left no part of the world unaffected, India being no exception. All economies in the world slowed down in the aftermath of this crisis. While India's exports to the countries of SE Asia have reduced, its imports from them have increased. This paper looks at the macro-economic variables of India so as to find out whether these variables are at a sound level and do not pose a problem in terms of destabilizing the economy as happened in SE Asia. The impact of the crisis on India's trade with these countries also has been examined. A few specific cases of corporate houses have been cited to illustrate the point that the crisis may be used as an opportunity rather than perceiving it only as a threat. The paper also lists some lessons that India could learn from the experiences of these countries, besides the perceptions of practising professionals about the crisis. - Reproduced
Keywords: Economic recession